FRAGMENTATION AND HARMONISATION IN INTERNATIONAL TRADE LAW: A LITERATURE REVIEW ON THE IMPACT OF REGIONAL TRADE AGREEMENTS ON THE WTO’S MULTILATERAL SYSTEM IN THE POST-PANDEMIC ERA - Gunawan Widjaja (Adisam Publisher, 2026)
This article examines the dynamics of fragmentation and harmonisation in international trade law in the wake of the COVID-19 pandemic through a literature review, focusing on the impact of Regional Trade Agreements (RTAs) on the multilateral system of the World Trade Organisation (WTO). The process of fragmentation is described in the context of the proliferation of RTAs, which gives rise to overlapping norms, inconsistent rules, and uncertainty for member and non-member states, particularly developing countries. On the other hand, this article asserts that RTAs can serve as “building blocks” for normative integration if designed in a manner compatible and transparent with WTO principles. Through adjustment mechanisms, dispute settlement, and plurilateral initiatives, the WTO demonstrates an adaptive capacity to maintain the coherence of the international trade law system amidst the proliferation of RTAs. Thus, this article concludes that fragmentation and harmonisation are not dichotomous but interrelated; the sustainability of the WTO’s multilateral system depends heavily on the capacity for coordination and harmonisation between regional and multilateral regimes in the post-pandemic era of global trade.